The Role of Teachers in Fostering Student Social Relationships to Mitigate Classroom Conflict - Hamda Hamidah (Darul Yasin Al Sys, 2026)
Harmonious social relationships are essential to an effective classroom environment; however, differences in students’ personalities, backgrounds, and social competencies can generate interpersonal conflicts that disrupt academic engagement. This study examines teachers’ roles in strengthening students’ social relationships and reducing classroom conflict, identifies common forms of conflict, and analyzes the factors that facilitate or hinder these efforts. A qualitative descriptive literature-review design was employed. Data were systematically gathered from relevant books and peer-reviewed journal articles and analyzed using content analysis. The findings indicate that teachers serve as role models, mentors, facilitators, and mediators by instilling core values, developing students’ social skills, and implementing peaceful conflict-resolution strategies. Effective implementation is supported by teacher competence, a positive school climate, parental involvement, and active student participation. Conversely, differences in student personalities, limited teacher time, insufficient parent–teacher communication, and inadequate conflict-management practices constrain these efforts. The study concludes that sustained teacher leadership, supported by coordinated institutional and parental involvement, is essential for fostering harmonious classroom relationships and minimizing interpersonal conflict. These findings contribute to understanding the multidimensional role of teachers in classroom conflict prevention and highlight the importance of integrated school-based strategies for strengthening students’ social competence and creating supportive learning environments.